2020
DOI: 10.1017/s1466252320000134
|View full text |Cite
|
Sign up to set email alerts
|

Genomics: the host's genotype and its relevance to bovine respiratory disease

Abstract: Genomic variation exists in cattle that affects their susceptibility to the complex of pathogens responsible for bovine respiratory disease (BRD). Heritability estimates and genome-wide association analyses (GWAA) support the role of host genomic variation in BRD susceptibility. Heritability estimates for BRD susceptibility range from 0.02 to 0.29 depending on the population, the definition of the disease, and the accuracy of diagnosis. GWAA have identified genomic regions (loci) associated with BRD in beef an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Heritability estimates for resistance to BRD were reported as low to moderate within the selected studies, which indicated that genetic selection may have potential to select animals that are more resistant to BRD. A genetics review article early in 2009 concluded that the heritability estimates for resistance to BRD were small, but two reviews recently published in 2020 revealed low to moderate heritability estimates [43][44][45]. These two studies also suggested that genetic selection could be utilized to enhance resistance to BRD.…”
Section: Discussionmentioning
confidence: 99%
“…Heritability estimates for resistance to BRD were reported as low to moderate within the selected studies, which indicated that genetic selection may have potential to select animals that are more resistant to BRD. A genetics review article early in 2009 concluded that the heritability estimates for resistance to BRD were small, but two reviews recently published in 2020 revealed low to moderate heritability estimates [43][44][45]. These two studies also suggested that genetic selection could be utilized to enhance resistance to BRD.…”
Section: Discussionmentioning
confidence: 99%